A Review of CommunityWorks Canada®: Toward Employability Among High School–Age Youth With Autism Spectrum Disorder. (October 2019) - Nicholas, David B.; Mitchell, Wendy; Zulla, Rosslynn; Solomatin, Evgeny; Qi, Siwei
CommunityWorks Canada ® is a 12-week (30-hour) program that provides social, communication, and job skill–building activities as well as peer mentorship to youth with autism spectrum disorder. Administration of a pre- and postprogram employment readiness measure (n = 76 participants) demonstrated positive changes as reflected by the participants' decreased concerns about their responsibility, flexibility, job skills, communication, self-view, and health and safety. Postprogram qualitative interviews and survey data collected from a range of program stakeholders (participants, parents, peer mentors, and community partners/employers) corroborated identified gains in personal development, employment exposure, work proficiency, and comfort in work settings. For community partners/employers and peer mentors, greater understanding about autism spectrum disorder and commitment to inclusive hiring reportedly resulted from program engagement. Implications and recommendations are offered.